SOLIDARITAS PAGUYUBAN PEDAGANG KAKI LIMA KABUPATEN PONOROGO DALAM MENGATASI KRISIS EKONOMI PADA MASA PANDEMI - Pertiwi, Nufikha Dwi (Paradigma, 2022)
Abstract The conflicts and problems faced by street vendors are complex. During the Covid-19 pandemic, a number of street vendors experienced a slump in terms of the economy. The government has implemented several policies aimed at reducing the covid-19 numbers which have an impact on the trading life of street vendors. Another impact that occurred was the regulation by Satpol PP officers due to the imposition of a curfew for selling. This has caused some street vendors to experience an economic crisis because there are few buyers. This condition makes solidarity between fellow traders closer because there are similar interests to maintain their trade. So that the formation of a street vendor association is able to provide a forum for traders if they find problems both internally and externally and still maintain solidarity during the pandemic. This research is a qualitative research using the Grounded Theory research approach of Strauss and Cobin. This research is located in Ponorogo Regency. The subjects of the study were the core management of the PERPEK-5 association and angkringan street vendors and snack sellers who sold late into the night. This study used two data collection techniques, namely primary and secondary. The data was then analyzed using three coding phases, namely open coding, axial coding, and selective coding. The theory used in this study is Emile Durkheim's Theory of Solidarity. The results showed that the PERPEK-5 street vendors association had a mechanical solidarity type and there was also an organic solidarity type. The two forms of solidarity are able to become a foundation for street vendors to increase the sense of family and cohesion in the Paguyuban. Keywords: Solidarity, Paguyuban, Street Vendors